Studentified areas as contested heterotopias: Findings from Southampton. Issue 2 (7th June 2018) - Brookfield, Katherine
Abstract : The ongoing "massification" of higher education in the UK has generated increased demand for student housing. Some of this demand is being met by new, purpose‐built student accommodation, but much is being met through an intensification of student properties in established "student areas, " and the expansion of student housing into neighbourhoods previously unaffected by high levels of student in‐migration in a process termed "studentification." Previous research indicates that the arrival of multiple student households in established residential areas creates conflict and adversely affects the non‐student population. Wishing to understand better these effects, this paper draws on focus group discussions completed with 11 diverse residents' groups based across Southampton, an English university city, which explored attitudes towards, and experiences of, studentification. Seeking a more robust theorisation of the sociospatial impacts of, and responses to, this process, the findings are considered in relation to Foucault's concept of "heterotopia." Reflecting previous findings, the residents' groups emerged as firm critics of studentification. Considered against Foucault's concept, it appeared that the "heterotopian" qualities of studentified areas formed the points of most concern. Implications for the future of studentified areas, and for the concept of heterotopia, are explored.